Friction and wear behaviors of MoS2-multi-walled-carbonnanotube hybrid reinforced polyurethane composite coating - Zhaozhu Zhang; Mingming Yang; Junya Yuan; Fang Guo; Xuehu Men (Friction)
Abstract MoS2-multi-walled-carbon-nanotube (MWCNT) hybrids containing two-dimensional MoS2 and one-dimensional MWCNTs were synthesized through a one-step hydrothermal reaction. X-ray-diffraction and transmission-electron-microscopy results demonstrated that MoS2 nanosheets were successfully synthesized, and uniformly anchored on the MWCNTs’ surfaces. Furthermore, the effects of the MoS2-MWCNT hybrids on the tribological performances of polyurethane composite coatings were investigated using a UMT-2MT tribo-tester. Friction and wear test results revealed that the friction coefficient and wear rate of a 3 wt% MoS2-MWCNT-1 filled polyurethane composite coating were reduced by 25.6% and 65.5%, respectively. The outstanding tribological performance of the MoS2-MWCNT-1 reinforced polyurethane composite coating was attributed to the excellent load-carrying capacity of the MWCNTs and good lubricant ability of MoS2. The surface morphologies of the worn surfaces and counterpart ball surfaces were investigated to reveal the wear mechanisms.